Add-on pricing, naive consumers, and the hidden welfare costs of education - Michael Kosfeld; Ulrich Schüwer (Institute for the Study of Labor (IZA), 2011)
Previous research shows that firms shroud high add-on prices in competitive markets with naive consumers leading to inefficiency. We analyze the effects of regulatory intervention via educating naive consumers on equilibrium prices and welfare. Our model allows firms to shroud, unshroud, or partially unshroud add-on prices. Results show that consumer education may increase welfare; however, it may also decrease welfare if education is insufficient to alter the equilibrium information and pricing strategy of firms. Educating consumers may do more harm than good and should thus only be considered if the regulator is sufficiently well informed about consumer and firm behavior.
urn:nbn:de:101:1-201111072755
Keywords: D40; D80; L50; 330; bounded rationality; competition; regulation; welfare; consumer protection; Betriebliche Preispolitik; Wettbewerb; Verbraucherschutz; Regulierung; Konsumentenverhalten; Lernen; Wohlfahrtsanalyse